2017
DOI: 10.1155/2017/2583717
|View full text |Cite
|
Sign up to set email alerts
|

Light Polarization Using Ferrofluids and Magnetic Fields

Abstract: We are presenting an experimental setup based on polarized light, enabling the visualization of the magnetic field of magnetic assemblies using a Hele-Shaw cell filled with ferrofluids. We have simulated the observed patterns with hypergeometric polynomials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 6 publications
(11 reference statements)
0
27
0
Order By: Relevance
“…For room temperature at T = 300 Kelvin the initial susceptibility of the ferrofluid of our system is given by the manufacturer at x0 = 2.62 in SI units 6 . Using the information from (2),(3),(6), (7) equations the information from the data in fig.8 and the data from the ferrofluid manufacturer 6 we plotted in fig.9 the frequency dependency of our ferrolens's magnetic susceptibility for three worse case scenarios values of τeff system relaxation times in order to draw our conclusions. From the above plot and considering the values for real-time operation requirement of the SSFM microscope (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For room temperature at T = 300 Kelvin the initial susceptibility of the ferrofluid of our system is given by the manufacturer at x0 = 2.62 in SI units 6 . Using the information from (2),(3),(6), (7) equations the information from the data in fig.8 and the data from the ferrofluid manufacturer 6 we plotted in fig.9 the frequency dependency of our ferrolens's magnetic susceptibility for three worse case scenarios values of τeff system relaxation times in order to draw our conclusions. From the above plot and considering the values for real-time operation requirement of the SSFM microscope (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Because the 10 nanometers (nm) average in size SPIONs of the ferrofluid superparamagnetic properties i.e. dipolar chains aligning to the magnetic field flux lines [5] and also their superabsorbing light properties [6,7], the magnetic field becomes visible. Notice as well, the object itself under magnetic viewing due to light bending becomes transparent and practically invisible i.e.…”
Section: Basicsmentioning
confidence: 99%
“…The detailed explanation of the positioning and measurements of the Hall sensor for the magnetic field of the compound magnets can be found in Figure 2 of Ref. [10]. The magnetic field of a cylinder magnet is a vector in the three-dimensional space, as shown in Figure 2.…”
Section: Condens Matter 2019 4 X For Peer Reviewmentioning
confidence: 99%
“…In this way, the image obtained from the Ferrolens in Figure 2a is related to the magnetic field obtained with the gaussmeter of Figure 4b, and the light pattern of Figure 2b is associated with the magnetic field of Figure 4d. One way to see directly what is happening inside the Ferrolens is by obtaining the polarimetry of the Ferrolens, see References [2][3][4]10] for more detailed discussions about the light polarization effects of this device. We observed that the nanoparticles create a diffracting grating following the orientation of the magnetic field, forming a needle-like structure locally.…”
Section: Condens Matter 2019 4 X For Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation